Multi-term fractional differential equations with nonlocal boundary conditions - Ahmad Bashir; Alghamdi Najla; Alsaedi Ahmed; Ntouyas Sotiris K. (Open Mathematics, 2018)
We introduce and study a new kind of nonlocal boundary value problems of multi-term fractional differential equations. The existence and uniqueness results for the given problem are obtained by applying standard fixed point theorems. We also construct some examples for demonstrating the application of the main results.